KINERJA KARYAWAN DITINJAU DARI DISIPLIN KERJA PADA PT. SUMBER HIDUP SEHAT SEMARANG - An Riwi Widyastuti; Novita Budiyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2022)
Employee performance is the result of work and work behavior that has been achieved in completing the tasks and responsibilities assigned to employees within a certain period of time. High performance performance is needed by employees to achieve company goals. This study aims to determine the relationship between work discipline and employee performance. The research method used is a quantitative, the collection of data using the work discipline scale and employee performance scale. The sample used amounted to 142 people. The sampling technique used is a saturated sampling technique. Analysis of the data used Spearman Rank Correlation. The results of this study indicate that there is a positive relationship between work discipline and employee performance. This is indicated by the value of F = 112,748; R = 0.668; R2 = 0.446 (p < 5%). The magnitude of the effect of work discipline on employee performance in this study is shown from the coefficient of determination R2 = 44.6%.